THE EFFECT OF SERVICE QUALITY ON KIOSK OWNER SATISFACTION AT THE TRADE SERVICE (PASAR CANDIPURO) - Vicky Andika Prahemas; Muhammad Firdaus; Muhaimin Dimyati (ABM: International Journal of Administration, Business and Management, 2021)
Broadly speaking, this study aims to determine the Effect of Licensing Service Quality Dimensions on Kiosk Owner Satisfaction at the Trade Service (Case Study at Candipuro Market, Lumajang Regency), this type of research is qualitative research, the sample in this study was 75 respondents, respondents in collecting this data is the owner of a kiosk at Candipuro Market, Lumajang Regency, the method of simple regression analysis, and the analytical method used in this study is descriptive analysis and multiple regression analysis. The research method used in this research is multiple linear regression, t test, f test and the coefficient of determination R2. The results of the research show that partially the assurance and empathy variables have no partial effect on the satisfaction of the kiosk owner at Candipuro market, this can be seen from the significant probability of the assurance and empathy variables. While the variables that have a significant effect are tangible, reliability, and responsiveness. So that the variable of Kiosk owner satisfaction is partially influenced by tangible, reliability and responsiveness (Ha is accepted and Ho is rejected). Keywords: Tangible Service Quality, Empathy, Responsiveness, Reliability and Assurance Kiosk Owner Satisfaction